Penerapan Hukum Bisnis bagi Pelaku Usaha UMKM di Wilayah Kota Banjarmasin - Mohammad Zainul; Periyadi Periyadi; Yulianis Safrinadiya Rahman; Sri Herlina (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to examine the role of business law on Micro, Small, and Medium Enterprises (MSMEs) in improving the economy in Banjarmasin City. The background of this community service is based on the importance of the role of business law in providing protection and support for MSMEs, which are the backbone of the local economy. The results of the study show that the effective application of business law can improve the competitiveness and sustainability of MSME businesses, as well as encourage economic growth in Banjarmasin City.